NADPH Oxidase-Derived ROS Induced by Chronic Intermittent Hypoxia Mediates Hypersensitivity of Lung Vagal C Fibers in Rats - Yang, Chang-Huan; Zhuang, Wei-Ling; Shen, Yan-Jhih; Lai, Ching Jung; Kou, Yu Ru (Frontiers in Physiology, 2016)
Obstructive sleep apnea, manifested by exposure to chronic intermittent hypoxia (CIH) and excess production of reactive oxygen species (ROS) in the airways, is associated with hyperreactive airway diseases. ROS, particularly when created by NADPH oxidase, are known to sensitize lung vagal C fibers (LVCFs), which may contribute to airway hypersensitivity pathogenesis. We investigated whether CIH augments the reflex and afferent responses of LVCFs to chemical stimulants and the roles of ROS and NADPH oxidase in such airway hypersensitivity. Rats were exposed to room air (RA) or CIH with/without daily treatment with MnTMPyP (a superoxide anion scavenger), apocynin (an NADPH oxidase inhibitor) or vehicle. At 16 h after their last exposure, intravenous capsaicin, adenosine or alpha,beta-methylene-ATP evoked an augmented apneic response in anesthetized rats with 14-day CIH exposure, compared to anesthetized rats with 14-day RA exposure. The augmented apneic responses to these LVCF stimulants were abolished by bilateral vagotomy or perivagal capsaicin treatment, which block LVCFs neural conduction and were significantly suppressed by treatment with MnTMPyP or apocynin, but not vehicle. Electrophysiological studies revealed that 14-day CIH exposure potentiated the responses of LVCFs to these stimulants. This effect was inhibited by treatment with MnTMPyP or apocynin treatment and was not seen in rats who received 7-day of CIH exposure. Biochemical analysis indicated that 14-day CIH exposure increased both lung lipid peroxidation, which is indicative of oxidative stress, and expression of the p47phox subunit in the membrane fraction of lung tissue, which is an index of NADPH oxidase activation. The former was prevented by treatment with either MnTMPyP or apocynin, while the later was prevented by treatment with apocynin only. These results suggest that 14-day CIH exposure sensitizes LVCFs in rats, leading to an exaggerated reflex and afferent responses to stimulants and that this sensitization is mediated via ROS generated by NADPH oxidase.